Carmelo E. Palumbo, Cuestiones de Teologías Etica y Filosofía, Editorial Cies, Buenos Aires, 1988, 187 pp. - Derisi, Octavio Nicolás (1989)
Fil: Derisi, Octavio N. Pontificia Universidad Católica Argentina; Argentina